Implementing directory services - Archie Reed (McGraw-Hill, 2000)
This book offers an explanation of important management concepts and justification for directory services; real world case studies from organizations ranging from small to large who have implemented directory services already; important information about interoperability of major standards, vendors, and tools; interactive tutorial to the sample application on the CD-ROM.